Pengembangan Deaf Light Bell untuk Mengetahui Informasi Adanya Tamu bagi Anak Tunarungu - M. Arief Wicaksana P; Asep Ahmad Sopandi (Jurnal Penelitian Pendidikan Khusus, 2023)
This research is motivated by the problem of limited hearing in the deaf which has an impact on delays in obtaining auditory information, such as not being able to hear guests calling, knocking on doors, or pressing an ordinary bell. Therefore, researchers developed the Deaf Light Bell which aims to make it easier for deaf children to find out information about guests coming to the house. This study uses the Research and Development (R&D) method with the Borg & Gall development model which consists of development steps which are limited to the fifth step, namely research and information collecting, planning, develop preliminary form of product, preliminary field testing, and main product revision. The product developed will be validated by three experts consisting of experts in the field of deaf children, experts in electrical engineering, and experts in adaptive technology. The data will be analyzed using percentage calculations. Based on the validation data obtained from the three experts, an average percentage of 96.4% can be obtained so that the Deaf Light Bell can be declared very feasible to use.